TEACHER STRATEGIES IN IMPROVING STUDENTS' READING INTEREST IN ARUN STATE ELEMENTARY SCHOOL LIBRARY, LHOKSEUMAWE CITY - Maulida, Rahmi; Safiah, Intan; Mislinawati, Mislinawati (Elementary Education Research, 2024)
This study aims to find out how the teacher's strategy is in increasing students' interest in reading at the SD Arun library, Lhokseumawe City. This research approach uses a qualitative approach to the type of descriptive research. The subjects in this study were teachers of grades IV, V and VI of SD and the objects of this study were students of grades IV, V and VI of SD Negeri Arun Lhokseumawe. Data collection techniques with observation, interviews, and documentation. The data analysis technique was carried out with the stages of data reduction, data display and drawing conclusions. Based on the results of the study it can be concluded that the teacher's strategy in increasing students' reading interest in the library of SD Negeri Arun is to design learning that encourages students to read in the library; giving literacy assignments that are carried out in the library room; give appreciation to students who often visit the library and who often borrow books; creating a comfortable library environment; increase the collection of reading materials; make rules; and running a school literacy program.